Thin Film Electrodes: Surface Evolution of Lithium Titanate upon Electrochemical Cycling Using a Combination of Surface Specific Characterization Techniques (Adv. Mater. Interfaces 11/2020). Issue 11 (10th June 2020) - Rikarte, Jokin; Acebedo, Begoña; Vilalta‐Clemente, Arantxa; Bonilla, Francisco; Wilkinson, Angus J.; Galceran, Montserrat; Lousa, Arturo; Rubio‐Zuazo, Juan; Muñoz‐Márquez, Miguel Ángel
Abstract : Highly oriented thin‐film electrodes are the best playground to better understand the evolution of the electrode‐electrolyte interfaces during battery operation. This is crucial to develop next generation batteries. In this cover the authors represent Li ions (spheres) from the electrolyte (fog) reaching LTO electrode surface (SEM image) as in cell operation. More details can be found in article number 1902164 by Miguel Ángel Muñoz‐Márquez and co‐workers.